HUBUNGAN SANITASI LINGKUNGAN DAN FAKTOR BUDAYA DENGAN KEJADIAN DIARE PADA ANAK BALITA DI DESA TORIYO KECAMATAN BENDOSARI KABUPATEN SUKOHARJO - Siti Amaliah (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2010)
Background: Occurrence of diarrhoea is high, specially for the five under years child at Bendosari Public Health Centre, which 30 % from Toriyo village.It caused probably by bed environment saniatation and cultural factor or habitual behaviour. Obyective: To analyse the correlation among environment sanitation and cultural factor with the  occurrence of diarrhea. Methods: The cross sectional design with cluster random sampling. The samples are 68 respondence of housewife.Independent variable are the environment sanitation and cultural factor. Dependent variable is incidence of diarrhea.Statistical analyse with Chi Square test. Result: The water supply using well dig 76,5 %, water of PDAM  23,5%. Faeces disposal with good latrine 45,58 %, no having latrine 54,42 %. Drinking water which not be braised 52,9%,stewed 47,1%.Cleaning the hand after defecate with soap 39,7%,  not with soap 60,3%; cleaning the hand with soap before eating 54,4%, not cleaning the hand 45,6 %. Treatment diarrhoea by self 58,8%, treatment by Public Health Centre 41,2 % There are significant correlation among clean water supply, coverage of bed latrine, drinking uncooked water, cleaning the hand with soap habits, and treatment by self with occurrence of diarrhoea (p < 0,05). Conclusion: There are significant correlation among environment sanitation and cultural factor with occurrence of diarrhoea.Keywords: diarrhoea, cultural factor, sanitation.